Dampak Penerapan Integrasi Antarmoda Angkutan Umum terhadap Jumlah Penumpang Angkutan Perkotaan Trans Jogja Trayek 6A, 6B, dan 15 - Kennyzyra, Muhammad; Nindyo Cahyo Kresnanto; Rizki Budi Utomo (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
The increasing needs of society have increased mobility and caused transportation problems, especially congestion. One solution is to promote the use of public transport. In Yogyakarta, the Trans Jogja Bus was introduced in 2008 as an effort to overcome traffic jams. This bus serves urban agglomeration areas with 140 units and 21 routes. One important step is the implementation of intermodal integration at Tugu Station, which connects Trans Jogja Buses with trains and KRL. This research aims to analyze the impact of this integration on increasing the number of passengers on routes 6A, 6B, and 15. The implementation of integration between public transport modes at Tugu City Yogyakarta Station can generally increase the number of passengers on Trans Jogja Urban Transport Routes 6A, 6B, and 15. Fluctuations The number of passengers on Trans Jogja Urban Transport Routes 6A, 6B, and 15 is caused by several factors such as the implementation of re-routing, teaching and learning activities at schools, red dates such as Christmas Day in December, and school holiday activities.